UJI AKTIVITAS ANTIBAKTERI MINYAK ATSIRI DAUN JERUK SAMBAL (Citrus x hystryx) TERHADAP Escherichia coli DAN Staphylococcus aureus - Yurisa Yurisa; Muhammad Agus Wibowo (Indonesian Journal of Pure and Applied Chemistry, 2019)
Essential oils of Jeruk Sambal leaves (Citrus x hystryx) have as antibacterial agents. This study aims to determine the antibacterial activity of dried Jeruk Sambal leaves originating from Sungai Kakap area against Escherichia coli and Staphylococcus aureus. Stages in this study were divided into two stages (1) isolation of volatile oil by steam distillation, (2) test the antibacterial activity by pitting diffusion method. Essential oil yield of 0.22% was obtained. The results of GC-MS analysis showed that the essential oil of Jeruk Sambal leaves dried has 4 main compounds, namely elemol (26.27%), β-eudesmol (14.47%), 2-β-pinene (13.84%) and linalool (7.77%). The test results showed that the antibacterial activity of essential oils of Jeruk Sambal leaves was more active in inhibiting the growth of S. aureus than E. coli bacteria.